2014
DOI: 10.4102/phcfm.v6i1.568
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic characteristics of persons committing suicide in Durban, South Africa: 2006–2007

Abstract: BackgroundSuicidal behaviour is a leading contributor to the burden of disease worldwide and varies widely between countries. South African figures are amongst the highest in the world, with recent trends indicating a disturbing rise, especially amongst the younger age groups, across all races.AimThis study analysed sociodemographic characteristics and trends relating to suicides committed in Durban, South Africa during the period of 2006–2007.MethodA retrospective analysis of suicidal deaths (during 2006–2007… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 25 publications
(34 reference statements)
8
21
0
Order By: Relevance
“…Seasonality in Suicide is reported from studies conducted around the globe (Naidoo & Schlebusch, 2014;Jia & Zhang, 2011;Dias et al, 2014) and the same was also observed in the present study. Hence suicide prevention strategies such as restriction of access to suicide methods, screening of risk population and strengthening of current medical emergency interventions could be initiated during the hotspot seasons of suicide.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Seasonality in Suicide is reported from studies conducted around the globe (Naidoo & Schlebusch, 2014;Jia & Zhang, 2011;Dias et al, 2014) and the same was also observed in the present study. Hence suicide prevention strategies such as restriction of access to suicide methods, screening of risk population and strengthening of current medical emergency interventions could be initiated during the hotspot seasons of suicide.…”
Section: Discussionsupporting
confidence: 90%
“…Suicide rate diverge for countries due to the difference in the social and cultural background, availability of mental health services, classification of death and accurate registration of suicidal deaths (Hawton & Heeringen, 2009). Globally suicide rate varies from 1.66 per100,000 population to 36.2 per100,000 population (ElHak et al, 2009;Naidoo & Schlebusch, 2014;Sun et al, 2013) and for Indian states it varies from 11.8 per100,000 population to 82.2 per100,000 population (Mohanty et al, 2007;Kumar et al, 2013;Badiye et al, 2014). Suicide rate 8.4 per100,000 population of Warangal district, Telangana observed in the present study seems to be much below suicide rate reported by other Indian studies.This could be due to difference in the source, suicide data was collected from only one tertiary care from Warangal district and hence undermines the true picture of the entire Warangal district.…”
Section: Discussionmentioning
confidence: 99%
“…This has put the livelihoods of many people at risk. Studies conducted in South Africa [36,38,39], Japan [40,41], Canada [40,41], South Korea [42] and Europe [35,37,40] had similar findings with deaths due to suicide and violence being common among males as a result of economic pressure, alcohol or drug abuse, and poverty.…”
Section: Discussionmentioning
confidence: 76%
“…Nevertheless, there has been an increase in the proportion of black suicide victims compared with that in Scri bante et al 's [9] study, indicating that suicide may be increasing among blacks. The increase in black suicide victims is also mentioned in the article by Naidoo and Schlebusch, [12] where research was done on suicide in Durban, KZN, another province of SA. More detailed research is required in this area.…”
Section: Discussionmentioning
confidence: 79%
“…[9] In the past 7 years research has been published on the profile of suicide in SA and Africa. [10][11][12][13][14] Most studies have shown that males commit suicide more often than females and that men tend to use more 'violent' methods. [1,5,9,11,[15][16][17][18] However, Scribante et al [9] reported a remarkably high incidence of suicide by firearms among women in Pretoria for 1997 -2000.…”
Section: Introductionmentioning
confidence: 99%